Electron cyclotron emission and electron cyclotron resonance heating (EC-16) : proceedings of the 16th joint workshop, Sanya, China, 12-15 April 2010 - Joint Workshop on Electron Cyclotron Emission and Electron Cyclotron Resonance Heating (16th : 2010 : Sanya, China); Prater, Ronald (Singapore : World Scientific)
Includes bibliographical references